PENENTUAN POLA PERUBAHAN SALINITAS PADA PENETASAN DAN PEMELIHARAAN LARVA UDANG GALAH (Macrobrachium rosenbergii) ASAL SUMATERA SELATAN - Obie Zikri; Ferdinand Hukama Taqwa; Marsi . (Universitas Sriwijaya, 2013)
ABSTRACT The purpose of this study was to determine the pattern of salinity changes on hatching eggs and rearing that the most effective for giant freshwater prawns from South Sumatra. The research was conducted in January to April 2012 in research institute of inland fisheries, Banyuasin South Sumatera. This research used four methods of treatment for the application of different salinity media water hatching eggs and larvae of water media. Method 1 of hatching and larvae rearing media at 12 ppt salinity maintained until postlarvae. Method 2 of hatching salinity media on 0pptÂ to 4 ppt, and larval rearing medium salinity increased as larvae aged 2 to 8 days from 4 to 12 ppt salinity and salinity of 12 ppt maintained until postlarvae. Methods 3 of hatching media on 0 ppt salinity, and larvae rearing medium salinity increased as larvae aged 1 to 6 days of salinity 0 to 12 ppt and at 17 days old larvae of 12 ppt salinity reduced gradually until 0 ppt to postlarvae. Methods 4 of hatching media on 0 ppt salinity, and larval rearing medium salinity increased as larvae aged 1 to 6 days in salinity 0 to 13 ppt and as larvae aged 17 days of 12 ppt salinity reduced gradually until 0 ppt to pascalarva. The results showed that application of the methods 4 was the most effective achieve the ability to live the longest until 24 days. Keywords : Macrobrachium rosenbergii, udang galah, salinitas